Ethernet's winning ways. - Kaplan, G. (IEEE spectrum)
Ethernet networks are winning big in manufacturing automation and process control-and for good reasons: they save money and they simplify operations. By 2003, the market for Ethernet networks that connect the factory to the higher levels of business operations and supply chain management is expected to reach US